Can neuromuscular fatigue threshold be determined by short and non-exhaustive bouts? - Fontes, E B; Okano, AH; de Paula Smirmaul, B; Altimari, L R; Goncalves, E M; Triana, RO; Moraes, A C (Brazilian Journal of Kinanthropometry and Human Performance, 2012)
The present study determined the neuromuscular fatigue threshold (NFT) using four different time-periods of analysis of the electromyographic signal and compared these estimations with critical power (CP). Fifteen healthy young men (73.6 plus or minus 5.1 kg, 177.8 plus or minus 7.0 cm, 23.4 plus or minus 5.2 years) performed 3-4 different severe constant workload trials until exhaustion on a cycle ergometer with simultaneous SEMG signals acquisition. The obtained data permitted NFT estimation with four different periods of analysis as follows: initial 30s (T30), 1min (T1), 2min (T2) and total time (TT), as well as CP. T30 and T1 were significantly higher than TT and CP and, T2 and TT did not differ between each other, and both were significantly higher than CP. In addition, TT was significantly correlated to CP (0.72; P < 0.05) and to T2 (0.58; P < 0.05). We conclude that NFT overestimates CP, independent of the time-period analysis used for its determination.Original Abstract: O presents estudo determinou o Limiar de Fadiga Neuromuscular - LFNM usando quatro diferentes periodos de analise do sinal eletromiografico e comparou essas estimativas com a Potencia Critica - PC. Quinze homens saudaveis do sexo masculino (73,6 plus or minus 5,1 kg, 177,8 plus or minus 7,0 cm, 23,4 plus or minus 5,2 anos) realizaram 3-4 testes severos de carga constante ate a exaustao em um cicloergometro com simultanea aquisicao de sinais SEMG. Os dados obtidos permitiram a estimativa de LFNM em quatro periodos diferentes: 30 segundos iniciais (T30), um minuto (T1), dois minutos (T2), tempo total (TT), assim como PC. T30 e T1 foram significativamente maiores do que TT e PC e, T2 e TT nao se diferiram entre si e foram maiores que PC. Alem disso, TT foi significativamente correlacionado com PC (0,72; P < 0,05) e com T2 (0,58; P < 0,05). Dessa forma, conclui-se que LFNM superestima PC, independente do tempo de analise utilizado para sua determinacao.